Synthesis of DI- and trialkylthiourea complexes of Cd, Mn and Ni as precursors for phosphonoacetic acid (PAA)-capped metal sulphide nanoparticles - Mlambo, Mbuso (My University, 2010)
Many studies on thiourea and its derivatives in different metal (II) complexes have confirmed that coordination is through the sulphur atom. The bonding of substituted thioureas to different metals was confirmed with a combination of spectroscopic studies such as IR and NMR spectroscopy and elemental analysis. A series of metal (II) di- and trialkylthioureas complexes have been synthesized and characterized. Their bonding through sulphur atoms rendered these complexes good precursors for the preparation of metal sulphide nanoparticles. Thermogravimetric analysis on the complexes was undertaken to check their suitability as precursors for the synthesis of nanoparticles and their potential as precursors for metal sulphide thin films using the chemical vapour deposition (CVD) technique and their general chemical and thermal stability. All the complexes reported in this work were used as single source molecular precursors for the synthesis of cadmium, manganese and nickel sulphide nanoparticles. In this study the investigation on the influence of capping agent and temperature on the size and morphology of nanoparticles was undertaken. Nanoparticles obtained by thermolysis of precursors in phosphonoacetic acid (PAA) were bigger in size and rod-shaped compared to smaller rods obtained in hexadecylamine (HDA). CdS nanoparticles prepared using PAA as a capping agent showed a huge blue-shift of the band edge from the bulk of 515 nm, compared to CdS nanoparticles obtained using HDA as a capping agent. When PAA was mixed with trioctylphosphine oxide (TOPO), a blue shift of band edges in all the bulk materials of different metal sulphides prepared was observed and the rod-shaped nanoparticles changed to spherical particles.